Analysis Policy Protection of Women and Children Tradecomparative Study of Indonesia Malaysia - Karolina Sitepu (International Conference of ASEAN Prespective and Policy (ICAP), 2018)
Trafficking of women and children is a global issue that is warmly discussed at present not only as a national crime but also a transnational offense which is a violation of human rights. The purpose of this study is to analyze the laws governing the prevention and protection of victims of trafficking of women and children in Malaysia and Indonesia. This research method uses normative juridical research that is comparative. By content analysis, it describes and analyzes the content material and the validity of data found in the legislation between two different legal systems. The results of this study found that in prevention efforts of PTPPO Indonesia and APOAPM Malaysia there are similarities. In the protection effort, there are significant differences where PTPPO Indonesia regulates the protection of both physical and material victims with the provision of compensation and restitution to the victims. While APOAPM Malaysia does not restrict it, both Lamaya time protection PTPPO Indonesia does not distinguish between citizen and foreign citizen otherwise APOAPM Malaysia differentiates between citizen two years while foreign citizen only three months. Conclusion expected to Malaysia add one article in APOAPM to give gantirugi and restitution to victims of trafficking. As per human rights there should be no discrimination in protection. Both countries are expected to increase the MOU in a sustainable manner to achieve the full protection as mandated by human rights.